Optimization of Permanent Magnet Synchronous Motor Design by Using PSO - Dal, Oznur; Yildirim, Merve; Kurum, Hasan (Ieee, 2019)
In this paper, an optimization of a Permanent Magnet Synchronous Motor (PMSM) with 12-pole and 18-slot surface magnet is realized by Particle Swarm Optimization (PSO) technique. Since there is no winding in the rotor of PMSMs, the efficiency of the motor is high. However, the windings in the stator cause the copper losses reducing the efficiency of the PMSM and creating heating problems. Therefore, the aim of this study is to decrease the copper losses of the PMSM and solve the heating problem. For this reason, the parameters of the winding structure are optimized by using PSO. Because the production stage of the PMSM is already completed, its geometric structure can not be changed. Only windings are optimized in this paper. Design equations of the PMSM and certain parameters are entered into MATLAB Simulation and the simulation is run by PSO. After the optimization results, electromagnetic analysis of the PMSM is realized by using ANSYS Maxwell 2D. Finally, the winding structure of the renewed motor is tested by experimental setup and the results are validated by the simulation results.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: permanent magnet synchronous motor; Matlab; particle swarm optimization; motor design; Anysys Maxwell 2D